Essential skills and strategies in higher education for the Fourth Industrial Revolution: A systematic literature review - Aboderin, O. S.; Havenga, M. (South African Journal of Higher Education, 2024)
The Fourth Industrial Revolution necessitates relevant initiatives to stay abreast. Higher education plays a pivotal role in providing nuanced opportunities for the future workforce and enabling students to address real-world problems in a complex world. Despite new developments, it is not clear how the Fourth Industrial Revolution will influence the educational sector. We followed a systematic review approach with the aim of providing a comprehensive view on crucial strategies and skills for the Fourth Industrial Revolution. We applied the processes of Evidence for Policy and Practice Information and Co-ordinating Centre as a guideline for conducting the systematic review and retrieved relevant articles published from 2017 to 2021. The results highlight that critical thinking is the most emphasised skill and student-centred teaching-learning strategies are essential for the Fourth Industrial Revolution and future demands. Implications for self-directed learning were also outlined.